Individualized Tailor-Made Dietetic Intervention Program at Schools Enhances Eating Behaviors and Dietary Habits in Obese Hispanic Children of Low Socioeconomic Status - Leticia Elizondo-Montemayor; Diana Moreno-Sànchez; Norma G. Gutierrez; Fabiola Monsivais-Rodriguez; Ubaldo Martinez; Ana C. Lamadrid-Zertuche; Martin M. Hernandez-Torre (The Scientific World Journal)
Hispanic children and those from low-socioeconomic status are predisposed to unhealthy eating habits and obesity. Aim. to implement an individualized, face-to-face, parent supported, and school-partnership dietetic intervention to promote healthy eating habits and decrease body mass index. Prospective school year dietetic intervention of 101 obese, Hispanic, low-socioeconomic school-age children representative of Monterrey, Mexico, consisted of anthropometrics, dietetic assessment, energy-restriction tailor-made daily menus, and parental education every three weeks. Student’s t-test was used for means comparison. A significant decrease was found in body mass index percentile (96.43±3.32 to 93.42±8.12/P=0.00) and energy intake/day of −755.7 kcal/day (P=0.00). Among other energy dense foods with significant decline in servings/day and servings/week were processed meats (3.13 ± 1.43 to 2.19 ± 1.04/P=0.00 and 5.60 ± 1.75 to 4.37 ± 2.10/P=0.00, resp.), saturated fat (1.47 ± 1.08 to 0.78 ± 0.79/P=0.00 and 2.19±2.18 to 1.1±1.36/P=0.00), sweetened beverages (2.79±1.99 to 1.42±1.21 and 6.21±1.72 to 3.89±2.80/P=0.00), and desserts and refined-grain bakery (1.99±1.54 to 1.32±1.59 and 2.85 ± 2.54 to 1.57 ± 2.20/P=0.00). There was a significant increase in servings/day and servings/week of water (2.98 ± 2.02 to 4.91 ± 2.37 and 6.62 ± 2.03 to 6.87 ± 0.91/P=0.00, resp.) and nutrient dense foods such as fruits (1.31 ± 0.89 to 1.66 ± 0.96 and 3.34 ± 2.24 to 4.28 ± 2.43/P=0.00) and fish and poultry (3.76 ± 2.15 to 4.54 ± 2.25/P=0.00). This intervention created healthy eating habits and decreased body mass index in a high risk population. Trial registration number: NCT01925976.